Exploring the nature of Parkinsonian rest tremor and the effects of common treatments on it: Stochastic process or chaotic behavior? - Sarbaz, Yashar; Pourakbari, Hakimeh (Biomedical signal processing and control, 2020)
•Parkinsonian rest tremor results in an involuntary oscillating movement with variable amplitude and frequency.•The nature of rest tremor is somehow complicated and also the effects of the treatments remained obscure.•The main objective of this study is to determine the dynamic characteristic of the Parkinsonian tremor using nonlinear analyses.•A combination of stochastic, periodic and chaotic dynamics is intrinsically present in tremor dynamic.•Effective treatments weaken the chaotic dynamic, and therefore, the stochastic behavior becomes more dominant. Parkinsonian rest tremor results in an involuntary oscillating movement with variable amplitude and frequency. The nature of rest tremor is somehow complicated and also the effects of the treatments remained obscure. The main objective of this study is to determine the dynamic characteristic of the Parkinsonian tremor using nonlinear data processing tools including phase space reconstruction, Delay Vector Variance (DVV), delta-epsilon analysis, Higuchi fractal dimension (HFD) and approximate entropy (ApEn). DVV and delta-epsilon analyses illustrate that tremor behavior is more similar to chaotic systems. Effective treatment alters its behavior toward stochastic processes. Based on the analysis, the value of the HFD for untreated tremor is around 1.7 and effective treatments reduces the value to about 1.1. In addition, ApEn of tremor signals is around 1.3 and by effective treatment it dips to 0.7. What is more, results of statistical tests for HFD and ApEn reveals that effective treatments lead to significant differences in the dynamical behavior of tremor in subjects with high amplitude (p < 0.05). To sum up, a combination of stochastic, periodic and chaotic dynamics is intrinsically present in tremor dynamic and as the severity of the disease increases, chaotic dynamics strengthen. Effective treatments weaken the chaotic dynamic, and therefore, the stochastic behavior becomes more noticeable and dominant. These results can be useful for tracking the disease progress and determining an appropriate dose of a drug for each patient. Moreover, our findings could lead to the development of a new tremor relief closed loop mechanism based on chaos to stochastic ratio.